2014
DOI: 10.1038/ncomms5737
|View full text |Cite
|
Sign up to set email alerts
|

The Glanville fritillary genome retains an ancient karyotype and reveals selective chromosomal fusions in Lepidoptera

Abstract: Previous studies have reported that chromosome synteny in Lepidoptera has been well conserved, yet the number of haploid chromosomes varies widely from 5 to 223. Here we report the genome (393 Mb) of the Glanville fritillary butterfly (Melitaea cinxia; Nymphalidae), a widely recognized model species in metapopulation biology and eco-evolutionary research, which has the putative ancestral karyotype of n ¼ 31. Using a phylogenetic analyses of Nymphalidae and of other Lepidoptera, combined with orthologue-level c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
268
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 214 publications
(295 citation statements)
references
References 69 publications
22
268
1
Order By: Relevance
“…In the other, six sets of S. litura chromosomes were fused, corresponding to six H. melpomene chromosomes (N = 21) 11 , and another eight S. litura chromosomes were fused, corresponding to four other H. melpomene chromosomes. These changes were consistent with previous reports on chromosome evolution among butterflies including Melitaea cinxia 12 and the moth Manduca sexta 13 …”
Section: Articlessupporting
confidence: 93%
“…In the other, six sets of S. litura chromosomes were fused, corresponding to six H. melpomene chromosomes (N = 21) 11 , and another eight S. litura chromosomes were fused, corresponding to four other H. melpomene chromosomes. These changes were consistent with previous reports on chromosome evolution among butterflies including Melitaea cinxia 12 and the moth Manduca sexta 13 …”
Section: Articlessupporting
confidence: 93%
“…hanski@helsinki.fi. populations for 222 SNPs distributed across the genome of the Glanville fritillary (33) to answer these questions. We compare 34 putative neutral SNPs with SNPs from potential candidate genes to identify outliers and hence potential targets for selection.…”
Section: Significancementioning
confidence: 99%
“…We have shown that, not only is there little evidence for substantial, fixed inversions between H. melpomene and H. cydno , but also that H. melpomene and H. erato , which last shared a common ancestor over 10 million years ago, have largely collinear genomes, and it is also known that there is substantial chromosomal synteny across the Nymphalids (Ahola et al. 2014). The association of multiple inversions with the wing pattern polymorphism in H. numata is all the more remarkable given the low background rate of inversions in these butterflies.…”
Section: Discussionmentioning
confidence: 99%